Geomorphological classification of the Thrace coasts after Valentin - ΞΕΙΔΑΚΗ Γ.; ΔΕΛΗΜΑΝΗ Π. (Bulletin of the Geological Society of Greece, 2001)
An attempt is made in this paper to elucidate the geologic evolution of the coastal zone at the North Aegean Sea (Thrace area) during the Holocene period and its géomorphologie classification. Various classification systems were applied but the Valentin system found to be the most applicable for the situation. Data were drawn from old topographic maps and aerophotos and from field observations. The main conclusion from this study is that the coasts of Thrace, and the North Aegean Sea, in their major stretch are retreating and submegning slowly(transgressive); most of them are formed by terrestrial deposits (river, torrents, etc) and are plain (open) coasts, according to Valentin classification. Even stretches of the Nestos River delta retreated by 100-150 m during the last forty years. The retrogression of the Thrace coasts is attributed mainly to engineering interference in the drainage system inland (construction of dams and irrigation canals, rearrangement or diversion of the river courses, embankment at rivers, etc.). All these works reduced drastically the sediments supply to the sea through the drainage system resulting in the erosion of the coasts. Technical interference near or on the shoreline like port construction, summer resorts, breakwaters, etc. also changed the dynamic equilibrium of the sediment transport along the shoreline, resulting in erosion at some stretches and deposition at others. There are but a few places where the coast is in equilibrium or even advancing e.g. estuaries and deltas of small torrents,the Mangana coast, the Mandra-Porto Lagos coast, etc.